Fabrication and characterization of polyvintl acetate slime phantom for T1-weighted, T2-weighted, and diffusion tensor magnetic resonance imaging - Chaw, Nurbranda (2020)
Polyvinyl acetate (PVA) is a type of adhesive that is squishy and viscous. The advantages of PVA materials are non-toxic, low cost, non-resistant to water and need simple preparation. The aim of the study is to explore the feasibility, suitability, and compatibility of PVA as tissue mimicking phantom for MRI studies. In this study, four PVA slime phantoms were fabricated with different additives that are water, oil, milk, and salt. Three other phantoms were prepared as controls materials that are water, oil, and milk. A total of seven phantoms were prepared and left for several days at room temperature to ensure no air bubbles formed in the phantoms. The T1, T2 and diffusion tensor imaging scan was performed using Philips Achieva 3 Tesla MRI system at the Department of Radiology, Hospital Universiti Sains Malaysia (HUSM). The signal intensity of the T1-weighted images (T1WI), T2-weighted images (T2WI), and diffusion-weighted images (DWI) of all phantoms were measured. Then, graphs of signal intensity vs TR and signal intensity vs TE were plotted to determine the T1 and T2 relaxation times, respectively. The diffusion coefficient (D) of the phantoms was also determined based on calculation using the specific equation. DTI parametric values of all phantoms were also recorded. The T1, T2, and D values were compared with normal and abnormal human tissues. The findings from this study showed that for all phantoms, T1 curves increases exponentially with TR while T2 curves decreases exponentially with increasing TE. The T1 and T2 relaxation as well as diffusion coefficient of the specific phantoms show similar characteristics to some human tissues. However, ghosting artefacts were observed in T2WI and DWI which need to be removed in future studies. To conclude, fabrication of the PVA slime phantom that mimics human tissues for MRI studies are feasible.